SOME ATTEMPTS TO DIAGNOSE POST-TRAUMATIC DEVIATIONS OF PARTICIPANTS OF COMBAT ACTIVITIES IN THE EARLY STAGES OF THEIR OCCURRENCE - Mas, N.; Floreskul, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The war in the East of Ukraine has taken the interest to the issues of post-traumatic disorders to a significantly high level. Due to the activity of the domestic scientists among the instruments of the psychologists-officers of the Armed Forces of Ukraine there’s a high variability of methods to define and identify the post traumatic disorders and deviations. They are represented both in the form of brief surveys for prior screening of the features of the post-traumatic stress disorder, states of emergency and depression and as well as in the form of the multifactor surveys to point out the severe reaction on stress, post-traumatic stress disorder, disorders in terms of adaptation, as well as other disorders under post-traumatic deviations. However, it is to be mentioned, that they are designed to identify the disorder that already obtained a nozological form. A number of surveys have shown that one of the main predictors of the post-traumatic stress disorder is a severe reaction to stress. Accordingly to the abovementioned, the development of a permanent and chronicle disorder could be prevented by identifying the post-traumatic disorders at the early stage of their appearance, previously to the development of the nozological disorder and a timely provision of the psychotherapeutical assistance. The article presents the results of the development of the individual semi-structured aimed interview and the assessment of its effectiveness as the method for diagnosis of post-traumatic disorders. The comparative analyses of the results of surveys with the results of the conducted interviews has manifested that the individual aimed semi-structured interview carries out the functions of diagnosis and could have a number of advantages compared with surveys.